Bidirectional circularly‐polarised loop linear array fed by slotted SIW. Issue 14 (1st July 2016) - Lu, Liang; Jiao, Yong‐Chang; Weng, Zi‐Bin; Ni, Tao; Zhang, Chi
Abstract : A novel multilayer bidirectional linear array with the same sense circularly polarised (CP) radiation patterns are proposed. The CP resonant unit consists of a pair of loops and two square patches added on their opposite corners. With a feeding slotted substrate integrated waveguide (SIW) sandwiched between two back‐to‐back mirror rotated resonant units, a radiating element is designed, and same sense bidirectional CP waves are generated. Along the longitude direction, the radiating elements are arranged alternately from the centre line of the slotted SIW. Then, an 8‐element linear array with uniform distribution is designed. Identical right‐hand CP waves are achieved in both front and back directions. The array is fabricated, and measured results are in good agreement with simulated ones.